The Effectiveness of Group Counseling Using SIBOL Techniques in the Academic Context - Christiana, Ratih; Mahmudi, Ibnu (KnE Social Sciences, 2022)
This study examines the effectiveness of group counseling using the self-instruction technique empirically based on observational learning (SIBOL) to foster a steady and great attitude in life as a student. The study used quantitative methods of “within-group or individual design” using equivalent time series, pre-test, post-test1, and post-test2 with a self-efficacy scale. The study included six students of Madiun with low selfefficacy in the academic context. Data analysis was done using the T-test calculations. It was found that group counseling through SIBOL techniques improved students’ selfefficacy, as evidenced by an increase in the students’ scores from pre-test to post-test2. Keywords: Group Counseling, SIBOL, Academic Contexts 1. Introduction